PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Akbar Panji Maulana, 09.05.51.0061; Indriyaningrum, Kis (Students Journal of Economic and Management, 2013)
This study analyzed the effects of work motivation, leadership, work environment on employee performance. The research object in this paper is PT.PLN (Limited) UIPJJB Semarang. SPSS version 16.0 software used for data analysis. The research objective was formulated to seek answers to the flow that affect employee performance. The results of his research are: (1) Motivation has a positive and significant impact on the performanceof an employee, the more likely motivation is given it will improve employee performance. (2) Leadership has a positive and significant effect on the performance of employees, the better leadership going on in the organization that will enhance employee performance. (3) The working environment has a positive and significant effect on employee performance, the better the work environment by providing safety and comfort of theemployees performance will increase.Key words: Work motivation, leadership, work environment and employee performance.